Assessment of the Impact of the Crisis on New PPI Projects : Update 5 - Izaguirre, Ada Karina (World Bank, Washington, DC, 2012)
New private infrastructure activity in developing countries recovered selectively in the third quarter of 2009. This review of new PPI projects sheds some light on recent activity and on the short-term impact of the financial crisis. Projects reaching financial or contractual closure face more difficult financial market conditions. Local state-owned banks, as well as multilateral and bilateral agencies, continue to be key financiers, and infrastructure sponsors are looking for new sources of funding such as local financing. Projects continue to be delayed or, to a lesser extent, canceled. The rate of project closure varies across developing regions, with investment in the third quarter higher in South Asia, stable in Latin America and East Asia and Pacific, and lower in the other three. The rate also varies across country income groups, with investment in the third quarter higher in lower-middle-income countries, stable in upper-middle-income countries, and lower in low-income countries. Greenfield projects continue to show growth in investment (and debt raised), while concessions and divestitures show a decline. Developing countries continue to tender and award new PPI projects. In conclusion, PPI investments have recovered in only few economies. While these success stories have boosted the totals, the vast majority of developing countries remain severely affected by the crisis. If large projects (US$1 billion or more) were excluded, almost all developing regions would have seen investment decline in the first three quarters of 2009 compared with the same period of 2008. South Asia was the only exception, thanks to the high level of activity in India. Among sectors, energy is the only one where investment grew for all project sizes, thanks to the activity in new power plants. There is also evidence of new projects being postponed and canceled because of the financial crisis.